2020
DOI: 10.1093/aob/mcaa155
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sugar metabolism genes in the nitrogen-dependent susceptibility of tomato stems toBotrytis cinerea

Abstract: Background and Aims The main soluble sugars are important components of plant defence against pathogens, but the underlying mechanisms are unclear. Upon infection by Botrytis cinerea, the activation of several sugar transporters, from both plant and fungus, illustrates the struggle for carbon resources. In sink tissues, the metabolic use of the sugars mobilized in the synthesis of defence compounds or antifungal barriers is not fully understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
3
9
0
Order By: Relevance
“…The specific involvement of soluble sugar metabolism in defence has been underlined by many studies [see Meyer et al ( 2007 ) for review], and the singular link between the relative fructose content in tomato stems and susceptibility to B. cinerea has been reported by Lecompte et al ( 2017 ). The dramatic fructose increase in plants under low N supply was consistent with the repression of fructokinase genes reported by Lacrampe et al ( 2021 ) and the overexpression of sucrose synthase providing fructose and UDP-glucose, the latter presumed to be consumed in cell wall reinforcement while the former accumulates.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The specific involvement of soluble sugar metabolism in defence has been underlined by many studies [see Meyer et al ( 2007 ) for review], and the singular link between the relative fructose content in tomato stems and susceptibility to B. cinerea has been reported by Lecompte et al ( 2017 ). The dramatic fructose increase in plants under low N supply was consistent with the repression of fructokinase genes reported by Lacrampe et al ( 2021 ) and the overexpression of sucrose synthase providing fructose and UDP-glucose, the latter presumed to be consumed in cell wall reinforcement while the former accumulates.…”
Section: Resultssupporting
confidence: 89%
“…It is therefore possible that high fructose concentrations participate in a direct or signalling defence mechanism against B. cinerea . The transcriptional activity of genes involved in sugar metabolism explored by Lacrampe et al ( 2021 ) showed that at high N, resistance was correlated with the rapid and transcient transcriptional activation of mitochondrial hexokinases HXK1 , HXK2 , the fructokinases FRK1 , FRK2 , FRK3 and the phosphofructokinase PFK1 , while the fructokinases where repressed in low-N plants. These results suggested that a high and early C flux into the downstream glycolysis and pentose phosphate pathways is required for resistance, which failed to happen under N deficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research hypothesized that overexpression of the gene encoding nonsymbiotic hemoglobin can interfere in the dynamics of ROS production and NO scavenging, and then reduce plant susceptibility to Meloidogyne incognita (Basso et al., 2022). Likewise, a recent study demonstrated that overexpression of fructokinase is associated with reduced susceptibility of tomato to B. cinerea infection, which might be due to that enhanced expression of fructokinases is beneficial for the recruitment of additional fructose in glycolysis and subsequent pathways for an effective defense (Lacrampe et al., 2021). Meanwhile, the expression level of fructokinase‐2 is more abundant in the resistant tomato lines than the susceptible lines during interaction with Ralstonia solanacearum (Dahal et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Opposing resource relationships may help to explain variable effects of nitrogen (N) supply on individual plant susceptibility to the necrotrophic fungal pathogen Botrytis cinerea (Lecompte et al, 2010 ). While various studies have captured inconsistent effects of N supply on B. cinerea infection across host species and pathogen strains (Hoffland et al, 1999 ; Lacrampe et al, 2020 ; Verhoeff, 1968 ), nonmonotonic relationships between N supply and both sporulation and pathogenicity were observed for single host‐single pathogen pairings (Abro et al, 2013 ). In this system, N supply has been linked to sugar‐dependent plant defenses and expression of B. cinerea virulence genes (Lacrampe et al, 2020 ), opposing processes that may help explain the nonmonotonic relationships.…”
Section: Examples Of Countervailing Effects Of Resource Supplymentioning
confidence: 99%